Diagnostic efficacy of fecal-based miR-92a for advanced colorectal neoplasia: a prospective multicenter screening trial - Jia-Chen Wang; Li Zhao; Xiang-Yang Yu; Ting-Ping Wu; Chang-Fa Xia; Ju-Fang Shi; Hui He; Zhi-Qi Chen; Dan Shi; Han Xue; Qi Ao; Shu-Ping Liao; et al. (Military Medical Research)
Abstract Background More efficacious, noninvasive screening methods are needed for advanced colorectal neoplasia. miR-92a is a reliable and reproducible biomarker for early colorectal cancer detection in stool samples. We compared the diagnostic efficacies of miR-92a, immunochemical fecal occult blood testing (FIT), and their combination (FIT + miR-92a) in a prospective multicenter screening trial. Methods Overall, 16,240 participants aged 30–75 years were enrolled between April 1, 2021, and December 31, 2023. A total of 15,586 participants returned samples available for both FIT and miR-92a tests. All those with positive, and a random selection of those with negative screening tests were recommended to undergo colonoscopy. Follow-ups were performed until participants completed the colonoscopic examination. A total of 1401 screen-positive and 2079 randomly selected screen-negative individuals completed colonoscopies. Primary outcomes included sensitivity, number needed to screen (NNS), Youden index and receiver operating characteristic area under the curve (AUC) for advanced adenomas and colorectal cancer [advanced neoplasia (AN)] for each screening modality in the diagnostic performance analysis. Results Colonoscopy was performed in 3480 individuals. The colonoscopy compliance rate was 47.8% for screen-positive individuals. The sensitivity of miR-92a versus FIT for AN was 70.9% versus 54.3% (P < 0.001), NNS was 24.7 versus 32.2 (P = 0.001), Youden index was 47.9% versus 35.0% (P < 0.001), AUC was 0.74 versus 0.67 (P = 0.010). FIT + miR-92a had a sensitivity of 85.4%, an NNS of 20.5, a Youden index of 47.9% and an AUC of 0.74 for AN. Conclusions For AN screening, miR-92a demonstrated better sensitivity, NNS, Youden index and AUC as compared with FIT. Compared with FIT, using miR-92a appears to be more efficient for population-based screening programs. Screening sensitivity for AN can be further enhanced if conditionally used in combination with FIT. Trial registration Chinese Clinical Trial Registration Number: ChiCTR2200065415.